Стан води в тканинах головного мозку та вплив на неї інкапсулювання кремнеземом - Крупська, Т. В.; Пакришень, С. В.; Сєров, О. В.; Волик, А. Т.; Туров, В. В. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2019)
The low-temperature 1H NMR spectroscopy was used to study the structure of hydrated water layers bound by brain tissue after ischemic stroke, as well as the effect of chloroform and trifluoroacetic acid on their structure. Almost all the water that is part of the brain tissue is bound, and its structure is close to the structure of bulk water, when each water molecule is involved in the formation of 2-3 hydrogen bonds. It is shown that chloroform, which is poorly soluble in water, can have a significant effect on the binding of water in the brain tissues and helps to reduce the energy of interaction of water with the internal phase boundaries. Additives of 20% trifluoroacetic acid (TFA) make it possible to differentiate intracellular water by its ability to dissolve strong acids. It was revealed that part of intracellular water does not dissolve TFAs well. In the presence of TFA, the contribution of domains and clusters of water of a smaller radius increases. Encapsulation of brain tissue with hydrophilic nanosilica leads to a significant increase in the value of interfacial energy of bound water, which occurs due to an increase in the contribution from strongly bound water. This is probably due to a significant decrease in the linear dimensions of tissue particles caused by the encapsulation process. Due to the large size of neurons, it can be assumed that tissue is divided into separate cells or small groups of adjacent cells. At the same time, significant changes in the characteristics of intercellular interactions are observed. Accordingly, the main maximum on the distribution curve DC(R) shifts to the region of smaller values and corresponds to clusters with a radius of R = 7 nm. The chloroform medium in the encapsulated sample stabilizes larger radius domains. This process is accompanied by a significant decrease in interfacial energy.